Seed, fertilizer and innovation in Bangladesh: Industry and policy issues for the future - Jaim, W. M. H.; Akter, Shaheen (International Food Policy Research Institute, 2012)
Bangladesh has achieved a remarkable success in food grain production in the recent past which has made the country nearly self-sufficient in food grain in normal years. Seed, fertilizer and irrigation technologies known as Green Revolution technologies have been playing major roles in the growth of agriculture production in Bangladesh. However, supply and markets of these modern inputs suffer from a lot of uncertainties. During the past, a lot of policy changes have been taken place to address these uncertainties, but a lot more to be done to face the future challenges of food security. In this context, in relation to Bangladesh this piece of work mainly intends to investigate the current structure of the seed and agricultural input industry; current structure and impact of the public agricultural research and extension systems; scope for improving access to new technologies by the resource poor farmers and the policy options to improve the ability of small-scale, resource poor farmers to access, and benefit from new technologies. The study is based mainly on secondary data and published reports as well as focus group discussions with farmers, input dealers, traders, etc.